Emerging Dynamics of the Medical Devices Sector in India - Tekade, Rakesh Kumar; Saraf, Shailendra; Bhattacharya, Pallab; Saraf, Swarnalata (Indian Journal of Pharmaceutical Education and Research)
With a current compounded annual growth rate of more than 16% and a projected market value of 12 billion US$, the medical device industry in the Indian subcontinent alone is projected to reach a market size of over 50 billion US$ by 2030. Despite being a vast market, emerging markets like India rely heavily on imports to meet most of their medical device needs. To bridge this gap, the government has envisioned developing innovative policies, indigenous facilities, practices, rules, and regulations to foster the production of medical devices. Keeping this in view, a series of initiatives have been rolled out, concealing the aspects related to classification, registration, manufacturing, pricing, sales, and market supplies. This review provides a comprehensive 360-degree understanding of the Dynamics of the medical device perspective, using a case study of an emerging market like India. The primary objective is to outline the ongoing regulatory amendments, new policy enforcement, adopted quality management tools, and quality standards required for medical device products. This review will also assist as a guide for stakeholders in subjects related to this sector, providing insight into the federal government's efforts to strengthen the country's medical device production capabilities, thereby improving access and affordability. It is anticipated that continued debate and effective action will benefit diverse sectors and ultimately enhance the worldwide development of medical device industries.
Keywords: Medical Devices; Medical Device Regulations; Government Initiatives; Federal Policies